Calculation of Fluid Flow Velocity in a Sloping Reservoir with Variable Datum Levels - Satiawati, Listiana; Dalimunthe, Yusraida Khairani; Widiyatni, Harin; Yulia, Prayang Sunny; Abdillah, Ridho (Sapta Arga Nusantara, 2025)
Knowledge and calculation of the nature of fluid flow in sloping reservoirs is very important in oil and gas exploration activities, because on its journey from the source rock (source rock) to migrate to the reservoir, the fluid will pass through rocks which are often non-structural in the form of slopes. in the reservoir. Therefore, calculating oil and gas flows for sloping reservoirs is very important. Slope fault theory is a new idea in searching for non-structural reservoirs, because it is increasingly difficult to find large-scale structural reservoirs. Therefore, structural-lithological reservoirs in slope areas have gradually become the focus of exploration, and on slopes are favorable places for oil and gas accumulation. To calculate fluid flow in a sloping reservoir using the derivation of the Darcy equation, the datum level is a variable that can be selected from the bottom point to the top point of the reservoir height. The problem is whether the flow velocity calculation results are the same for any point. This is to make measurements easier in oil and gas fields. This research will prove that random selection of the datum level does not change the flow velocity value of the flowing fluid. Firstly, in this article, the fluid flow velocity will be calculated using the three datum level points used. Calculations use the usual/manual method with a calculator and it is proven that the calculation results are the same. Then all points from the bottom to the top of the reservoir height will be calculated. The method that will be used uses a lot of data to prove the results are the same. Because there are quite a lot of calculations, the calculations will be calculated numerically by coding using the Fortran program. It turns out from the programming results that the fluid flow rate in a sloping reservoir has the same value using datum level data calculated from the bottom to the height of the reservoir with an increase of every 1 ft. So it is concluded that calculations using datum levels can be done anywhere in the height range of oil and gas reservoirs.